Taxonomy of Fulgoraecia melanoleuca (Fletcher, 1939), (Lepidoptera: Epipyropidae) in India, a biological control agent of Pyrilla perpusilla (Walker) (Hemiptera: Lophopidae) - Kumar, Rajesh; Mittal, Vishal; Chutia, Preetirekha; Ramamurthy, V.v. (Zootaxa, 2015)
The parasitic lepidopteran insect, Fulgoraecia melanoleuca (Fletcher) has been reported as an ectoparasitoid of Pyrilla perpusilla (Walker) from the Indian subcontinent. For the first time, the complete morphology, field biology, egg laying behavior, larval pupal, and adult morphology, including male and female gentialic features, are described and illustrated.